Synthesis and Activity Test of Cu/ZnO/Al2O3 for the Methanol Steam Reforming as a Fuel Cellâs Hydrogen Supplier - Makertihartha, IGBN; Subagjo, Subagjo; Gunawan, Melia Laniwati (ITB Journal Publisher, LPPM ITB, 2009)
TheÂ synthesisÂ ofÂ hydrogenÂ fromÂ hydrocarbonsÂ throughÂ theÂ steam reformingÂ ofÂ methanolÂ onÂ Cu/ZnO/Al2O3Â catalystÂ hasÂ beenÂ investigated.Â This process is assigned to be one of the promising alternatives forÂ fuel cell hydrogen process source. Hydrogen synthesis from methanol can be carried out by means ofÂ methanolÂ steamÂ reformingÂ whichÂ isÂ aÂ gasÂ phaseÂ catalyticÂ reactionÂ between methanol and water. In this research, theÂ Cu/ZnO/Al2O3Â catalystÂ prepared by the dryÂ impregnationÂ wasÂ used.Â TheÂ specificÂ surfaceÂ areaÂ ofÂ catalystÂ wasÂ 194.69 m2/gram.TheÂ methanolÂ steamÂ reformingÂ (SRM)Â reactionÂ wasÂ carriedÂ outÂ by means of the injection of gas mixture containing methanol and water with 1:1.2 mol ratio and 20-90 mL/minute feedÂ flow rate to a fixed bed reactor loaded by 1 g of catalyst. The reaction temperature was 200-300 Â°C, and the reactor pressure was 1 atm. PrecedingÂ the reaction, catalyst was reduced in the H2/N2Â mixture at 160Â Â°C.Â ThisÂ studyÂ showsÂ thatÂ atÂ 300Â Â°CÂ reactionÂ temperature,Â methanol conversionÂ reachedÂ 100%Â atÂ 28Â mL/minuteÂ gasÂ flowÂ rate.Â ThisÂ conversion decreasedÂ significantlyÂ withÂ theÂ increaseÂ ofÂ gasÂ flowÂ rate.Â Meanwhile,Â the catalyst prepared for SRMÂ was stable in 36 hours of operation at 260Â Â°C. The catalyst exhibited a good stability although the reaction condition was shifted to a higher gas flow rate.